ANALISIS SOSIAL DAN EKONOMI KEMISKINAN DI KELURAHAN SUNGAI LILIN KECAMATAN SUNGAI LILIN KABUPATEN MUSI BANYUASIN - Eka Roostartina (Department of Development Economics, Universitas Sriwijaya, 2013)
The phenomenon of poverty can not be avoided, although the development has reduced the number of poor but have not been able to eliminate poverty. It's time poverty alleviation programs based on the factors that influence it, because the factors causing poverty each region possess different characteristics, thus the fight against poverty also vary. Data was collected through interviews using questionnaires directly to respondents, the sample is taken using the Slovin formula derived from the data of Social Protection of the target households in 2008. The analysis showed that 86 percent of households are in productive age, 87 percent of family heads did not complete primary education junior, education significantly affect family income (family heads who had not completed junior high school is very poor households and poor), number of family members did not significantly affect family income, the income of other family members significantly affect family income and employment as laborers did not significantly affect family income. The role of local government is very important because the more aware of the characteristics of poverty in their areas. To address the low education of poor families needed improvements and increased access to education for free. Orientation of education aimed at creating graduates who are able to become entrepreneurs and create jobs. It takes a variety of additional training to increase skills and the development of productive assets by providing capital assistance. Keywords: poverty, education, occupation, income amount and family members